Blockchain-Based Market Procurement of Reactive Power - Stefan Haselbarth; Oskar Winkels; Kai Strunz (IEEE Access, 2023)
A flexible and adaptable market procurement of reactive power has the potential to improve network efficiency, voltage stability, and operational costs. In Europe, such a dynamic procurement must be in accordance with the European Union directive EU 2019/944 on non-frequency ancillary services. In accordance with this situation, a blockchain-based framework of market procurement of reactive power is proposed and presented in this paper. The devised framework is in alignment with the European Union’s directive to establish a non-discriminatory, transparent, and free market. Moreover, the blockchain-based framework is applicable at all network levels and allows for the variety of different distributed resources to participate. A two-layer blockchain topology is proposed to overcome scalability and transaction time issues. The first main-layer blockchain acts as the agent for trust and guarantees the immutability of data as well as the remuneration of participating market players. The second-layer blockchain facilitates direct access to tendering processes or auctions, fast transactions, and low transaction fees for involved stakeholders. Additionally, a decentralized oracle network is proposed to integrate external data into the second-layer blockchain. Data required for verifying the physical reactive power transactions are delivered by smart meters. The entire procurement process is automated by deploying smart contracts at the various blockchain layers. Thus, in principle, the involved stakeholders are the system operators and market players. For the purpose of validation, the holistic market procurement process is demonstrated and analyzed in a hardware-in-the-loop environment involving reactive power procurement at the distribution network level.